2008
DOI: 10.1152/ajprenal.00408.2007
|View full text |Cite
|
Sign up to set email alerts
|

Albumin-stimulated DNA synthesis is mediated by Ca2+/PKC as well as EGF receptor-dependent p44/42 MAPK and NF-κB signal pathways in renal proximal tubule cells

Abstract: Lee YJ, Han HJ. Albumin-stimulated DNA synthesis is mediated by Ca 2ϩ /PKC as well as EGF receptor-dependent p44/42 MAPK and NF-B signal pathways in renal proximal tubule cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…These observations are consistent with previous results that demonstrated that cells under ER stress can stave off apoptosis by activating JNK (38) or NF-B (50). Our previous report (27) showed that MAPKs and NF-B activation are involved in the regulation of SGLTs in PTCs, in which NF-B phosphorylation stimulated by p44/42 MAPKs, p38 MAPK, and JNK activations is responsible for the increases of SGLT expression. In addition, p44/42 MAPKs are an important downstream effector mechanism for cellular protection by ER stress in renal epithelial cells (18).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These observations are consistent with previous results that demonstrated that cells under ER stress can stave off apoptosis by activating JNK (38) or NF-B (50). Our previous report (27) showed that MAPKs and NF-B activation are involved in the regulation of SGLTs in PTCs, in which NF-B phosphorylation stimulated by p44/42 MAPKs, p38 MAPK, and JNK activations is responsible for the increases of SGLT expression. In addition, p44/42 MAPKs are an important downstream effector mechanism for cellular protection by ER stress in renal epithelial cells (18).…”
Section: Discussionmentioning
confidence: 96%
“…hand precipitating a proapoptotic or inflammatory environment that ultimately leads to tubular atrophy and renal failure (6,8,19,27,43). Proteinuria is a common hallmark of glomerular pathology, and the magnitude of proteinuria is a well-known adverse prognostic factor in a wide variety of kidney diseases.…”
mentioning
confidence: 99%
“…Albumin-mediated renoprotection may be explained by several mechanisms, including maintaining renal perfusion [6,31,32], promoting proximal tubular integrity and function [22,33-38], binding of endogenous toxins and nephrotoxic drugs [39-42], and preventing oxidative damage and binding and delivering protective lysophosphatidic acid [34,36,43,44]. The important renoprotective role of serum albumin was underscored by a recent meta-analysis showing hypoalbuminemia to be a potent independent risk factor both for AKI and for death following the development of AKI [45].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of renal proximal tubular cell to albumin activates EGFR, leading to nuclear factor-κB activation and cell cycle progression (124). In human renal epithelial cells, albumin activates EGFR and ERK via ROS production and this signaling cascade is required for interleukin-8 induction (125).…”
Section: Kidneymentioning
confidence: 99%